The Libyan slave trade: a study on the responsibility of the Libyan government and relevant regional and international bodies based on international standards - Nyirongo, Rachael (Department of Public Law, 2020)
In 2015, the “Migrant Crisis” caused panic in Europe, with Europe experiencing a high number of migrants arriving from the sea. Some countries increasing their bans on migrants and other limiting their migrant intake, the repercussions faced by the migrants in Libya have been atrocious. Soon, there were various reports exposing the abuse that the migrants were facing en route to Europe, one of these being slavery. Libya is the main transit route for migrants on their way to Europe and as a result, Libya has been facing a large influx of migrants. These migrants travel to Libya with the aim of being smuggled across the sea in the hopes of penetrating European borders and seeking asylum. Unfortunately, these migrants have found themselves to be victims of grave human rights abuses, including the crime of slavery. In 2017, CNN aired the first video footage that exposed the slave trade taking place in Libya. The thesis focuses on the potential accountability of the Libyan Government, the African Union, the European Union and the United Nations. It focuses on the relevant regional and international instruments and principles, including the Responsibility to Protect doctrine. Through various reports, it looks at the abuses the migrants are facing and which parties are responsible for these abuses. The thesis finds that whilst all bodies contributed to the crisis, and all bodies reacted, there are clear indications of some of them not working at their full capacity. However, as the thesis deals mainly with regional and international bodies, their accountability is limited